To evaluate the inequalities given the condition \( n = -15 \), we will substitute \( n \) into each inequality and see which one holds true.
-
First Inequality: \[ -n - 4 > -10 \] Substituting \( n = -15 \): \[ -(-15) - 4 > -10 \implies 15 - 4 > -10 \implies 11 > -10 \quad \text{(True)} \]
-
Second Inequality: \[ -n - 4 < 10 \] Substituting \( n = -15 \): \[ -(-15) - 4 < 10 \implies 15 - 4 < 10 \implies 11 < 10 \quad \text{(False)} \]
-
Third Inequality: \[ -n - 4 < -10 \] Substituting \( n = -15 \): \[ -(-15) - 4 < -10 \implies 15 - 4 < -10 \implies 11 < -10 \quad \text{(False)} \]
-
Fourth Inequality: \[ -n - 4 > 10 \] Substituting \( n = -15 \): \[ -(-15) - 4 > 10 \implies 15 - 4 > 10 \implies 11 > 10 \quad \text{(True)} \]
So, we have:
- The first inequality is true.
- The second inequality is false.
- The third inequality is false.
- The fourth inequality is true.
Thus, both the first and the fourth inequalities are true when \( n = -15 \). However, since we are only to select one option, the first inequality: \[ -n - 4 > -10 \] is a valid answer.
The answer from the multiple choices that is true is:
- \( -n - 4 > -10 \)